Hasil Belajar Keterampilan Servis Atas pada Permainan Bolavoli Ditinjau dari Perspektif Pembelajaran - Bela Murdian Putra (Jurnal Penelitian Pendidikan, 2016)
The significant aspect of the volleyball competition is to be accurate in a service. Surely,this was affected by some factors including a motoric ability. Therefore, this researchwas carried out to reveal the influence of direct learning approach compared to indirectlearning approach viewed from the motoric ability. The experimental method within 2X2factorial design was the most practical way for this issue. Then, the population werestudents of SMAN Negeri 2 Pacitan Ngadirojo Academic Year 2015/2016 who consistedof 60 students. Furthermore, the sampling technique used was the purposive randomsampling. The predetermined samples were 20 students who have the high motoricability and 20 students who have the low motoric ability. The variables in the researchwere independent variables consisting of two factors: the manipulative variable andattributive variables and the dependent variable. The research results showed that: (1)there was a significant difference between those taught using direct learning approachand those taught using indirect learning approach toward servicing on the volleyball.Direct learning approach was better than the indirect approach to learning; (2) therewas the significant difference between those who have the high motoric ability and thosewho have the low motoric ability in volleyball servicing result. The students who have ahigh motoric ability got better learning results than those having the low motoric ability;(3) there was the significant interaction effect between learning approach and motoricability towards learning the result of overhand volleyball service. (a) For those having ahigh motoric ability were appropriate to use the direct learning approach otherwise (b)for those having low motoric ability were more appropriate to use the indirect learningapproach.